2019
DOI: 10.1007/978-3-030-17705-8_11
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Usability of a Chatbot for Mental Health Care

Abstract: The aim of this paper is to assess the usability of a chatbot for mental health care within a social enterprise. Chatbots are becoming more prevalent in our daily lives, as we can now use them to book flights, manage savings, and check the weather. Chatbots are increasingly being used in mental health care, with the emergence of "virtual therapists". In this study, the usability of a chatbot named iHelpr has been assessed. iHelpr has been developed to provide guided self-assessment, and tips for the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
78
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 11 publications
2
78
0
2
Order By: Relevance
“…Users considered the following components of chatbots useful: real-time feedback [ 33 , 45 , 50 ], diary [ 52 ], weekly summary [ 42 ], presenting the helpline during the conversation [ 36 ], and psychoeducation [ 52 ]. Some studies found that virtual agents embodied in chatbots are useful for motivating users to use chatbots [ 34 ], establishing a relationship with them [ 35 ], and feeling supported by them [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Users considered the following components of chatbots useful: real-time feedback [ 33 , 45 , 50 ], diary [ 52 ], weekly summary [ 42 ], presenting the helpline during the conversation [ 36 ], and psychoeducation [ 52 ]. Some studies found that virtual agents embodied in chatbots are useful for motivating users to use chatbots [ 34 ], establishing a relationship with them [ 35 ], and feeling supported by them [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The ease of use and usability of chatbots were assessed in 20 studies [ 33 , 34 , 36 , 39 , 43 , 46 - 51 , 53 - 61 ]. Participants in 15 studies rated the overall ease of use of chatbots as high [ 36 , 39 , 43 , 47 - 50 , 53 - 55 , 57 - 61 ]. A total of 5 studies assessed the usability of chatbots [ 34 , 36 , 46 , 51 , 56 ], and it was rated high in all these studies (ranging from 69 to 88.2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations